Homoepitaxial growth of 3-inch single crystalline AlN boules by the physical vapor transport process - Wang, Qikun; Lei, Dan; Huang, Jiali; Sun, Xiaojuan; Li, Dabing; Zhou, Zhenxiang; Wu, Liang (Frontiers in Materials, 2023)
Aluminum nitride (AlN) single crystals with a diameter of 3-inch (76 mm) were successfully grown by the physical vapor transport (PVT) method. The initial homoepitaxial growth run was performed on an AlN seed sliced from a Φ51 mm AlN boule, and diameter enlargement was conducted iteratively via the lateral expansion technique until a Φ76 mm boule was achieved. During the diameter expansion growth runs, the crystal shape transitioned from a hexagonal pyramid to a cylindrical pyramid. After the standard slicing and wafering processes, the as-obtained substrates were characterized by high-resolution X-ray diﬀraction (HRXRD), preferential chemical etching, and ultraviolet–visible–near-infrared (UV-vis-NIR) spectroscopy. The characterization results revealed that the AlN substrates showed good crystallinity and excellent UV transparency, although a slight quality deterioration was observed when the crystal size was expanded from Φ51 to Φ76 mm, while the deep-UV (DUV) transparency remained very similar to that of the AlN seeds. The Φ76 mm AlN boules obtained in this study are an important milestone towards achieving Φ100 mm (4-inch) AlN, which are essential for the rapid commercialization of DUV optoelectronics and ultra-wide bandgap (UWBG) electronics.